Investigating the impact of corrosion on behavior and failure modes of reinforced concrete slabs: an experimental and analytical study - Yang, Zhihong (2024)
Corrosion of steel reinforcement significantly reduces the load-carrying capacity of reinforced concrete (RC) flat slabs, making them more vulnerable to punching shear failure. This type of failure can lead to sudden and catastrophic collapse of the structure. Despite its critical implications, research on this topic remains limited, and a mechanical model to estimate the load-displacement behavior of RC flat slabs with corroded reinforcements is currently lacking. In this paper, experimental work on corroded RC slabs under punching shear loading was conducted. To investigate the impact of corrosion on the structural behavior of reinforced concrete (RC) flat slabs, eight specimens, including both corroded and uncorroded controls, were subjected to load testing. The study focused on key performance indicators including punching shear strength, stiffness, crack patterns, failure modes, and energy dissipation capacity. Additionally, an analytical study based on the newly developed Critical Shear Crack Theory (CSCT) was conducted to understand the behavior of corroded RC slabs. Experimental results indicated a significant reduction in the punching shear strength of corroded slabs. Moreover, as corrosion progressed, a notable shift in failure mode from punching shear to flexural failure was observed. The proposed CSCT model demonstrated good agreement between the experimentally obtained and analytically predicted load-displacement curves.